Acid and alkali resistant cable sheath material and preparation method thereof
By using chlorosulfonated polyethylene with ethylene-vinyl acetate copolymer, composite filler and flame retardant in cable sheath material, combined with specific treatment methods, the acid and alkali resistance of cable sheath material is solved. The combustion and processability issues achieve high performance and good use characteristics.
Patent Information
- Application Number
- CN202411448417.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The cable sheath material in existing electric vehicle charging piles has insufficient acid and alkali resistance, flame retardancy, cold resistance, oil resistance and processability, and the chlorosulfonated polyethylene has low hardness and poor processability, making it difficult to meet multiple items at the same time. Performance requirements.
Using a combination of chlorosulfonated polyethylene and ethylene-vinyl acetate copolymer, composite filler, plasticizer and flame retardant, the hardness, acid and alkali resistance of the cable sheath is improved through specific mixing and treatment methods. and processability, including the preparation of intercalated hydrotalcite powder and carbon black dispersions to improve the compatibility and dispersion of fillers, and improve the dispersion and binding of flame retardant by surface treatment.
The cable sheath has achieved high acid and alkali resistance, flame retardancy, cold resistance, oil resistance and processability, suitable softness and hardness, significantly improved tensile strength and elongation at break, and significantly improved flame retardancy and aging resistance. , processability and performance have been significantly improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable sheath materials, and in particular to an acid and alkali resistant cable sheath material and a preparation method thereof. Background Art
[0002] With the rapid development of my country's electric vehicle industry, the demand for electric vehicle charging piles is increasing. Considering the complexity of the use scenarios of electric vehicle charging piles, the performance requirements for the materials used in electric vehicle charging piles are also getting higher and higher, especially the performance requirements for the cable sheath in the electric vehicle charging piles. The cable sheath is required to have excellent acid and alkali resistance and aging resistance, and the cable sheath must have appropriate hardness and softness, and have excellent strength, flame retardancy, cold resistance, oil resistance, and tear resistance.
[0003] The commonly used materials for cable sheaths in electric vehicle charging piles are polyolefin thermoplastic elastomers or polyurethane thermoplastic elastomers, but polyolefin thermoplastic elastomers have poor flame retardancy, oil resistance, and tear resistance, and polyurethane thermoplastic elastomers have poor acid and alkali resistance, which affects the performance of cable sheaths in electric vehicle charging piles.
[0004] Chlorosulfonated polyethylene is made from low-density polyethylene or high-density polyethylene through chlorination and chlorosulfonation. After chlorination and chlorosulfonation, some hydrogen atoms in polyethylene are replaced by chlorine and sulfonic acid groups. Chlorosulfonated polyethylene is a white or yellow elastomer with excellent acid and alkali resistance and aging resistance. In addition, due to the presence of sulfonic acid groups, it can undergo a controllable cross-linking reaction. The cross-linked chlorosulfonated polyethylene also has excellent strength, cold resistance, and oil resistance. Therefore, compared with polyolefin thermoplastic elastomers or polyurethane thermoplastic elastomers, chlorosulfonated polyethylene is more suitable as a material for cable sheaths in electric vehicle charging piles.
[0005] However, when chlorosulfonated polyethylene is used as the material of cable sheath in electric vehicle charging piles, the following problems exist: first, the hardness of chlorosulfonated polyethylene is low, resulting in low hardness of the prepared cable sheath and susceptibility to mechanical damage; second, the higher the chlorine content of chlorosulfonated polyethylene, the better the oil resistance, but the worse the cold resistance, therefore, it is difficult for the prepared cable sheath to have excellent oil resistance and cold resistance at the same time; third, chlorosulfonated polyethylene is a pseudoplastic fluid, and its non-Newtonian properties weaken as the temperature increases, but chlorosulfonated polyethylene is prone to decomposition at high temperatures, resulting in a decrease in the performance of chlorosulfonated polyethylene, so in the processing of chlorosulfonated polyethylene, the processing temperature needs to be controlled, resulting in poor processability of chlorosulfonated polyethylene; fourth, chlorosulfonated polyethylene has poor flame retardancy.
[0006] In response to the above problems, the inventors have tried the following solutions: for the first problem, chlorosulfonated polyethylene and ethylene-vinyl acetate copolymer are mixed to improve the hardness of the prepared cable sheath; for the second problem, chlorosulfonated polyethylene with a high chlorine content is mixed with a filler to ensure that the prepared cable sheath has excellent oil resistance and cold resistance; for the third problem, chlorosulfonated polyethylene is mixed with a plasticizer to improve the processability of chlorosulfonated polyethylene; for the fourth problem, chlorosulfonated polyethylene is mixed with a flame retardant to improve the flame retardancy of the prepared cable sheath.
[0007] However, when using chlorosulfonated polyethylene as raw material to prepare cable sheath according to the above solution, the following problems still exist: first, the acid and alkali resistance of ethylene-vinyl acetate copolymer is poor, which will affect the acid and alkali resistance of the prepared cable sheath; second, when selecting fillers, carbon black or white carbon black with a high specific surface area is generally selected, but the surface energy of the above fillers is large and easy to agglomerate, and the compatibility of the fillers with chlorosulfonated polyethylene is poor, resulting in the fillers being difficult to disperse evenly, and the bonding force between the fillers and the chlorosulfonated polyethylene is poor, which will affect the processability of the chlorosulfonated polyethylene and the performance of the prepared cable sheath. Although surfactants or silane coupling agents can be used to modify the surface of the fillers to improve the compatibility of the fillers with chlorosulfonated polyethylene, the surfactants and the fillers are combined through intermolecular forces, and under high temperature and high shear, the surface The active agent is easy to detach from the surface of the filler; although the silane coupling agent can introduce organic groups on the surface of the filler in the form of chemical bonds by reacting with the hydroxyl groups on the surface of the filler, the filler is easy to agglomerate. During the surface modification process, it is difficult for the silane coupling agent to enter the agglomerated filler, resulting in uneven surface modification and the problem of filler agglomeration. Third, the plasticizer also has compatibility problems with chlorosulfonated polyethylene. If the amount added is too small, the effect of improving the processability is not obvious. If the amount added is too large, it will affect the performance of the prepared cable sheath. Fourth, the commonly used flame retardants are hydrates of metal oxides with high specific surface areas and zinc borate, which are also easy to agglomerate themselves or agglomerate with fillers, and the amount used is large. There is also a problem of poor compatibility with chlorosulfonated polyethylene, which will also affect the processability of chlorosulfonated polyethylene and the performance of the prepared cable sheath. Summary of the invention
[0008] In view of the shortcomings of the prior art, the present invention provides an acid and alkali resistant cable sheath material and a preparation method thereof. The prepared cable sheath material not only has good acid and alkali resistance, but also has appropriate hardness, high strength, aging resistance, flame retardancy, cold resistance, oil resistance, tear resistance, and good processability.
[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0010] An acid and alkali resistant cable sheath material, composed of the following raw materials, by weight: 100-105 parts of chlorosulfonated polyethylene, 36-40 parts of ethylene-vinyl acetate copolymer, 60-65 parts of composite filler, 14-16 parts of plasticizer, 11-13 parts of acid absorber, 11-12 parts of flame retardant, 6-7 parts of stabilizer, 3.4-3.6 parts of cross-linking agent, 3.8-4 parts of auxiliary cross-linking agent, 2.4-2.6 parts of antioxidant, 1.3-1.5 parts of coupling agent, 1-1.2 parts of antioxidant;
[0011] The chlorine content of the chlorosulfonated polyethylene is 35.4%, the sulfur content is 1.1%, and the Mooney viscosity is ML 1+4 100℃ is 55;
[0012] The vinyl acetate content of the ethylene-vinyl acetate copolymer is 50%, and the Mooney viscosity is ML 1+4 100℃ is 27;
[0013] The preparation method of the composite filler comprises the following steps: preparing intercalated hydrotalcite powder, preparing carbon black dispersion, mixing once, and mixing twice;
[0014] The method for preparing intercalated hydrotalcite powder comprises the following steps: preparing a hydrotalcite powder dispersion, and intercalating the dispersion;
[0015] The method for preparing the hydrotalcite dispersion comprises adding the hydrotalcite and deionized water into an ultrasonic oscillator, controlling the ultrasonic oscillation frequency of the ultrasonic oscillator to 20-25 kHz, and ultrasonically oscillating at room temperature for 30-40 minutes to obtain the hydrotalcite dispersion;
[0016] In the preparation of the hydrotalcite dispersion, the mass volume ratio of hydrotalcite to deionized water is 10-11 g: 200-250 mL;
[0017] The average particle size of the hydrotalcite is 300-400nm;
[0018] The intercalation comprises adding hexadecyltrimethylammonium bromide and deionized water into a reactor, controlling the stirring speed of the reactor to 300-400 rpm, stirring at room temperature for 10-15 minutes, adding ammonia water and anhydrous ethanol, continuing stirring for 20-30 minutes, adding melamine and hydrotalcite dispersion, continuing stirring for 35-45 minutes, controlling the temperature of the reactor to 50-55° C., continuing stirring for 5-5.5 hours, transferring the reactor into a centrifuge, controlling the centrifugal speed of the centrifuge to 7000-8000 rpm, centrifuging for 10-11 minutes, washing the precipitate with deionized water for 3-4 times, and vacuum drying the precipitate to obtain intercalated hydrotalcite;
[0019] In the intercalation layer, the mass volume ratio of hexadecyltrimethylammonium bromide, deionized water, ammonia water, anhydrous ethanol, melamine, and hydrotalcite dispersion is 47-50g:1900-2000mL:600-650mL:900-950mL:16-18g:1300-1400mL;
[0020] The mass concentration of the ammonia water is 25%;
[0021] The method for preparing the carbon black dispersion comprises adding carbon black and deionized water into an ultrasonic oscillator, controlling the ultrasonic oscillation frequency of the ultrasonic oscillator to 20-25 kHz, and ultrasonically oscillating at room temperature for 30-40 minutes to obtain the carbon black dispersion;
[0022] In the preparation of the carbon black dispersion, the mass volume ratio of carbon black to deionized water is 30-35 g:500-550 mL;
[0023] The average particle size of the carbon black is 100-200nm;
[0024] The primary mixing includes adding intercalated hydrotalcite powder and deionized water into a reactor, controlling the stirring speed of the reactor to 300-400 rpm, stirring at room temperature for 30-40 min, adding hexadecyltrimethylammonium bromide, continuing stirring for 30-40 min, adding carbon black dispersion, continuing stirring for 1-1.5 h after the addition is completed, transferring to a centrifuge, controlling the centrifugal speed of the centrifuge to 9000-10000 rpm, centrifuging for 10-11 min, washing the precipitate 3-4 times with deionized water and vacuum drying to obtain a primary mixture;
[0025] In the primary mixing, the mass volume ratio of intercalated hydrotalcite powder, deionized water, hexadecyltrimethylammonium bromide, and carbon black dispersion is 25-30 g:900-1000 mL:8-9 g:850-950 mL;
[0026] The addition rate of the carbon black dispersion is 20-25 mL / min;
[0027] The secondary mixing is performed by adding the primary mixture and deionized water into a reactor, controlling the stirring speed of the reactor to 300-400 rpm, stirring at room temperature for 30-40 min, adding an aqueous solution of sodium dodecylbenzenesulfonate, continuing to stir for 1.5-2 h after the addition is completed, transferring to a centrifuge, controlling the centrifugal speed of the centrifuge to 9000-10000 rpm, centrifuging for 10-11 min, washing the precipitate 3-4 times with deionized water and vacuum drying to obtain a composite filler;
[0028] In the secondary mixing, the mass volume ratio of the primary mixture, deionized water, and sodium dodecylbenzenesulfonate aqueous solution is 85-90 g: 2700-3000 mL: 3300-3500 mL;
[0029] The addition rate of the sodium dodecylbenzenesulfonate aqueous solution is 90-100 mL / min;
[0030] The mass concentration of the sodium dodecylbenzenesulfonate aqueous solution is 1%;
[0031] The plasticizer is composed of oxidized polyethylene wax, trioctyl trimellitate, and dioctyl sebacate, wherein the mass ratio of oxidized polyethylene wax, trioctyl trimellitate, and dioctyl sebacate is 3-3.5:20-25:5-6;
[0032] The acid absorber is active magnesium oxide with an average particle size of 200 nm;
[0033] The method for preparing the flame retardant comprises the following steps: mixing and surface treatment;
[0034] The mixing, adding magnesium hydroxide and zinc borate into a mixing kettle, controlling the stirring speed of the mixing kettle to 50-100 rpm, stirring for 30-40 minutes, to obtain a mixture;
[0035] In the mixing, the mass ratio of magnesium hydroxide to zinc borate is 80-85:10-12;
[0036] The average particle size of the magnesium hydroxide is 100-200nm;
[0037] The average particle size of the zinc borate is 100-200 nm;
[0038] The surface treatment comprises adding the mixture, the first portion of Tween 80 and the first portion of deionized water into a reactor, controlling the stirring speed of the reactor to 200-400 rpm, stirring at room temperature for 1-1.5 hours, transferring the mixture into a centrifuge, controlling the centrifugal speed of the centrifuge to 9000-10000 rpm, centrifuging for 10-11 minutes, washing the precipitate with deionized water for 3-4 times and vacuum drying the precipitate to obtain a primary filter residue; then adding all the primary filter residues, phytic acid and the second portion of deionized water into a reactor, controlling the stirring speed of the reactor to 200-400 rpm, stirring at room temperature for 2-2 ... and transferring the mixture into a centrifuge. In a centrifuge, the centrifugal speed of the centrifuge is controlled to 9000-10000 rpm, centrifuged for 10-11 minutes, the precipitate is washed 3-4 times with deionized water and vacuum dried to obtain a secondary filter residue; then all the secondary filter residues and the second portion of Tween 80 and ethyl acetate are added to a reactor, the stirring speed of the reactor is controlled to 200-400 rpm, stirred at room temperature for 1.5-2 hours, transferred to a centrifuge, the centrifugal speed of the centrifuge is controlled to 10000-11000 rpm, centrifuged for 10-11 minutes, the precipitate is washed 3-4 times with ethyl acetate and vacuum dried to obtain a flame retardant;
[0039] In the surface treatment, the mass volume ratio of the mixture, the first portion of Tween 80, the first portion of deionized water, phytic acid, the second portion of deionized water, the second portion of Tween 80, and ethyl acetate is 90-95 g: 18-20 g: 2700-3000 mL: 17-19 g: 2700-3000 mL: 22-25 g: 2700-3000 mL;
[0040] The stabilizer is composed of zinc methacrylate, calcium stearate, zinc stearate and barium stearate, wherein the mass ratio of zinc methacrylate, calcium stearate, zinc stearate and barium stearate is 2.8-3:1-1.2:0.3-0.4:1-1.3;
[0041] The cross-linking agent is di-tert-butyl diisopropylbenzene peroxide;
[0042] The auxiliary cross-linking agent is trimethylolpropane trimethacrylate;
[0043] The antioxidant is one of antioxidant 1035 or antioxidant 1010;
[0044] The coupling agent is composed of silane coupling agent KH550 and silane coupling agent Si-69, wherein the mass ratio of silane coupling agent KH550 to silane coupling agent Si-69 is 2-2.5:1;
[0045] The antioxidant is one of antioxidant MB, antioxidant OD and antioxidant TPPD.
[0046] A preparation method of the aforementioned acid- and alkali-resistant cable sheath material, specifically comprising: weighing all raw materials according to the specified mass fractions, adding chlorosulfonated polyethylene, ethylene-vinyl acetate copolymer, composite filler, plasticizer, acid absorber, flame retardant, stabilizer, antioxidant, coupling agent, and anti-aging agent into an internal mixer, controlling the internal mixer temperature to 90-95°C, and the internal mixer speed to 60-80rpm, and after internal mixer mixing for 25-30min, cooling the mixture to 78-80°C at a cooling rate of 3-4°C / min, adding a crosslinking agent and an auxiliary crosslinking agent, and continuing internal mixer mixing for 7-8min, and transferring the mixture into an open mixer for thinning, rubber swinging, and calendering to obtain the acid- and alkali-resistant cable sheath material.
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] (1) The acid and alkali resistant cable sheath material of the present invention uses a composite filler and a flame retardant as raw materials, wherein the preparation method of the composite filler is to first prepare an intercalated hydrotalcite powder, specifically, to mix hexadecyltrimethylammonium bromide, ammonia water, melamine, and a hydrotalcite powder dispersion liquid, and then self-assemble, insert the self-assembled supramolecules between the layers of the hydrotalcite powder, and modify the surface of the hydrotalcite powder to introduce cationic charges to obtain an intercalated hydrotalcite powder; then, the intercalated hydrotalcite powder and hexadecyltrimethylammonium bromide are dispersed in deionized water, and then a carbon black dispersion liquid is added. The intercalated hydrotalcite powder is used as a dispersant to promote the dispersion of carbon black and the combination with hexadecyltrimethylammonium bromide, thereby combining hexadecyltrimethylammonium bromide on the surface of carbon black, introducing cationic charges on the surface of carbon black, and obtaining a mixture of intercalated hydrotalcite powder with cationic charges on the surface and carbon black with cationic charges on the surface, i.e., a primary mixture; finally, the primary mixture is dispersed in deionized water, and then sodium dodecylbenzene sulfonate and dodecane are added. Sodium dodecylbenzene sulfonate carries anionic charge and can self-assemble. It is combined with sodium dodecylbenzene sulfonate on the surface of the primary mixture to obtain a composite filler coated with a double layer of surfactant, thereby achieving the following technical effects: first, through the double layer of surfactant coating, the agglomeration of the composite filler can be avoided, the binding property of the surfactant and the composite filler is improved, and the desorption of the surfactant during high temperature processing is avoided, thereby improving the processability of the prepared cable sheath; second, the composite filler can promote the combination of chlorosulfonated polyethylene and ethylene-vinyl acetate copolymer, thereby improving the hardness, tensile strength, elongation at break, tear resistance, acid and alkali resistance, cold resistance, and oil resistance of the prepared cable sheath; third, the intercalated hydrotalcite in the composite filler will absorb heat and desorb at high temperature, play a role in heat insulation, thereby improving the aging resistance of the prepared cable sheath. In addition, the melamine in the supramolecule can also play a flame retardant role, thereby reducing the amount of flame retardant and improving the flame retardancy of the prepared cable sheath. The preparation method of the flame retardant is to first mix magnesium hydroxide and zinc borate to obtain a mixture, then use Tween 80 to surface treat the mixture, combine Tween 80 on the surface of the mixture, then use phytic acid to surface treat the mixture, continue to combine phytic acid on the surface of the mixture, and then use Tween 80 to surface treat the mixture, continue to combine Tween 80 on the surface of the mixture to obtain a flame retardant, the surface of the flame retardant is combined with two layers of Tween 80, the middle of Tween 80 is phytic acid, and the phytic acid plays a molecular bridging role. The flame retardant has the following technical effects: first, the two layers of Tween 80 can improve the dispersibility of the flame retardant and the binding force with other materials, and the plant can also improve the binding force between the two layers of Tween 80, thereby improving the processability, flame retardancy, hardness, tensile strength, elongation at break, tear resistance, acid and alkali resistance, aging resistance, cold resistance, and oil resistance of the prepared cable sheath; second, phytic acid can also improve the flame retardancy of the flame retardant, thereby further reducing the amount of the flame retardant and improving the flame retardancy of the prepared cable sheath;
[0049] (2) The acid and alkali resistant cable sheath material prepared by the present invention has appropriate hardness and Shore A hardness (15s) of 78-80 degrees;
[0050] (3) The acid and alkali resistant cable sheath material prepared by the present invention has high strength, a tensile strength of 19.1-20.8 MPa, and an elongation at break of 604-620%;
[0051] (4) The acid and alkali resistant cable sheath material prepared by the present invention has good flame retardancy and an oxygen index of 33.4-34.2%;
[0052] (5) The acid and alkali resistant cable sheath material prepared by the present invention has good tear resistance and a tear strength of 52.6-54.3 kN / m;
[0053] (6) The acid- and alkali-resistant cable sheath material prepared by the present invention has good acid and alkali resistance. The acid- and alkali-resistant cable sheath material prepared by the present invention is completely immersed in a sulfuric acid aqueous solution with a mass concentration of 30%. After being completely immersed at room temperature for 24 hours, the retention rate of tensile strength is 98.4-99.0%, and the retention rate of elongation at break is 94.0-94.7%; the acid- and alkali-resistant cable sheath material prepared by the present invention is completely immersed in a sodium hydroxide aqueous solution with a mass concentration of 40%. After being completely immersed at room temperature for 24 hours, the retention rate of tensile strength is 99.0-99.5%, and the retention rate of elongation at break is 94.7-95.3%;
[0054] (7) The acid- and alkali-resistant cable sheath material prepared by the present invention has good aging resistance. After aging the acid- and alkali-resistant cable sheath material prepared by the present invention with hot air at 136°C for 168 hours, the retention rate of tensile strength is 99.0-100.0%, and the elongation at break is 94.1-95.5%;
[0055] (8) The acid- and alkali-resistant cable sheath material prepared by the present invention has good cold resistance. After freezing the acid- and alkali-resistant cable sheath material prepared by the present invention at -50°C for 48 hours, the retention rate of tensile strength is 97.4-98.1%, and the elongation at break is 91.7-93.3%;
[0056] (9) The acid- and alkali-resistant cable sheath material prepared by the present invention has good oil resistance. After the acid- and alkali-resistant cable sheath material prepared by the present invention is completely immersed in air compressor oil at 70°C for 24 hours, the retention rate of tensile strength is 93.2-94.7%, and the elongation at break is 86.6-87.2%;
[0057] (10) The acid- and alkali-resistant cable sheath material prepared by the present invention has good processability, and the dispersion state of carbon black in the acid- and alkali-resistant cable sheath material of the present invention is 9.0-9.2 level. DETAILED DESCRIPTION
[0058] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0059] Example 1
[0060] An acid and alkali resistant cable sheath material, composed of the following raw materials, by weight: 100 parts of chlorosulfonated polyethylene, 36 parts of ethylene-vinyl acetate copolymer, 60 parts of composite filler, 14 parts of plasticizer, 11 parts of acid absorber, 11 parts of flame retardant, 6 parts of stabilizer, 3.4 parts of cross-linking agent, 3.8 parts of auxiliary cross-linking agent, 2.4 parts of antioxidant, 1.3 parts of coupling agent, 1 part of antioxidant;
[0061] The chlorine content of the chlorosulfonated polyethylene is 35.4%, the sulfur content is 1.1%, and the Mooney viscosity is ML 1+4 100℃ is 55;
[0062] The vinyl acetate content of the ethylene-vinyl acetate copolymer is 50%, and the Mooney viscosity is ML 1+4 100℃ is 27;
[0063] The preparation method of the composite filler is:
[0064] 1. Preparation of intercalated hydrotalcite:
[0065] (1) Preparation of hydrotalcite dispersion: Add 10 g of hydrotalcite and 200 mL of deionized water into an ultrasonic oscillator, control the ultrasonic oscillation frequency of the ultrasonic oscillator to 20 kHz, and ultrasonically oscillate at room temperature for 30 min to obtain a hydrotalcite dispersion;
[0066] The average particle size of the hydrotalcite is 300 nm;
[0067] (2) Intercalation: 47 g of hexadecyltrimethylammonium bromide and 1900 mL of deionized water were added to a reactor, the stirring speed of the reactor was controlled to 300 rpm, and the mixture was stirred at room temperature for 10 min. 600 mL of ammonia water and 900 mL of anhydrous ethanol were added, and the mixture was stirred for 20 min. 16 g of melamine and 1300 mL of hydrotalcite dispersion were added, and the mixture was stirred for 35 min. The temperature of the reactor was controlled to 50 ° C. and the mixture was stirred for 5 h. The mixture was transferred to a centrifuge and the centrifugal speed of the centrifuge was controlled to 7000 rpm. The mixture was centrifuged for 10 min. The precipitate was washed 3 times with deionized water and dried under vacuum to obtain intercalated hydrotalcite.
[0068] The mass concentration of the ammonia water is 25%;
[0069] 2. Preparation of carbon black dispersion: Add 30 g of carbon black and 500 mL of deionized water into an ultrasonic oscillator, control the ultrasonic oscillation frequency of the ultrasonic oscillator to 20 kHz, and ultrasonically oscillate at room temperature for 30 minutes to obtain a carbon black dispersion;
[0070] The average particle size of the carbon black is 100 nm;
[0071] 3. Primary mixing: add 25 g of intercalated hydrotalcite and 900 mL of deionized water into a reactor, control the stirring speed of the reactor to 300 rpm, stir at room temperature for 30 min, add 8 g of hexadecyltrimethylammonium bromide, continue stirring for 30 min, slowly add 850 mL of carbon black dispersion, control the addition speed to 20 mL / min, continue stirring for 1 h after the addition is completed, transfer to a centrifuge, control the centrifugal speed of the centrifuge to 9000 rpm, centrifuge for 10 min, wash the precipitate 3 times with deionized water and vacuum dry to obtain a primary mixture;
[0072] 4. Secondary mixing: 85 g of the primary mixture and 2700 mL of deionized water were added to a reactor, the stirring speed of the reactor was controlled to 300 rpm, and the mixture was stirred at room temperature for 30 min. 3300 mL of sodium dodecylbenzene sulfonate aqueous solution was slowly added at a speed of 90 mL / min. After the addition was completed, the mixture was stirred for 1.5 h. The mixture was transferred to a centrifuge, the centrifugal speed of the centrifuge was controlled to 9000 rpm, and the mixture was centrifuged for 10 min. The precipitate was washed 3 times with deionized water and vacuum dried to obtain a composite filler.
[0073] The mass concentration of the sodium dodecylbenzenesulfonate aqueous solution is 1%;
[0074] The plasticizer is composed of oxidized polyethylene wax, trioctyl trimellitate, and dioctyl sebacate, wherein the mass ratio of oxidized polyethylene wax, trioctyl trimellitate, and dioctyl sebacate is 3:20:5;
[0075] The acid absorber is active magnesium oxide with an average particle size of 200 nm;
[0076] The preparation method of the flame retardant is:
[0077] 1. Mixing: Add 80 g of magnesium hydroxide and 10 g of zinc borate into a mixing kettle, control the stirring speed of the mixing kettle to 50 rpm, and stir for 30 min to obtain a mixture;
[0078] The average particle size of the magnesium hydroxide is 100 nm;
[0079] The average particle size of the zinc borate is 100 nm;
[0080] 2. Surface treatment: 90 g of the mixture, 18 g of Tween 80, and 2700 mL of deionized water were added to a reactor, the stirring speed of the reactor was controlled to 200 rpm, and the mixture was stirred at room temperature for 1 h. The mixture was transferred to a centrifuge, the centrifugal speed of the centrifuge was controlled to 9000 rpm, and the mixture was centrifuged for 10 min. The precipitate was washed 3 times with deionized water and vacuum dried to obtain a primary filter residue. Then, all the primary filter residues, 17 g of phytic acid, and 2700 mL of deionized water were added to a reactor, the stirring speed of the reactor was controlled to 200 rpm, and the mixture was stirred at room temperature for 2 h. , transferred to a centrifuge, the centrifugal speed of the centrifuge was controlled to 9000rpm, centrifuged for 10min, the precipitate was washed 3 times with deionized water and vacuum dried to obtain a secondary filter residue; then all the above secondary filter residues, 22g Tween 80, and 2700mL ethyl acetate were added to a reactor, the stirring speed of the reactor was controlled to 200rpm, stirred at room temperature for 1.5h, transferred to a centrifuge, the centrifugal speed of the centrifuge was controlled to 10000rpm, centrifuged for 10min, the precipitate was washed 3 times with ethyl acetate and vacuum dried to obtain a flame retardant;
[0081] The stabilizer is composed of zinc methacrylate, calcium stearate, zinc stearate, and barium stearate, wherein the mass ratio of zinc methacrylate, calcium stearate, zinc stearate, and barium stearate is 2.8:1:0.3:1;
[0082] The cross-linking agent is di-tert-butyl diisopropylbenzene peroxide;
[0083] The auxiliary cross-linking agent is trimethylolpropane trimethacrylate;
[0084] The antioxidant is antioxidant 1035;
[0085] The coupling agent is composed of silane coupling agent KH550 and silane coupling agent Si-69, wherein the mass ratio of silane coupling agent KH550 to silane coupling agent Si-69 is 2:1;
[0086] The antioxidant is antioxidant MB.
[0087] A preparation method of the aforementioned acid- and alkali-resistant cable sheath material, specifically comprising: after weighing all raw materials according to the specified mass fractions, adding chlorosulfonated polyethylene, ethylene-vinyl acetate copolymer, composite filler, plasticizer, acid absorber, flame retardant, stabilizer, antioxidant, coupling agent, and antioxidant into an internal mixer, controlling the internal mixer temperature to 90°C, and the internal mixer speed to 60rpm, after internal mixer mixing for 25 minutes, cooling to 78°C at a cooling rate of 3°C / min, adding a cross-linking agent and an auxiliary cross-linking agent, and continuing internal mixer mixing for 7 minutes, transferring to an open mixer, and performing thin pass, rubber swing, and calendering to obtain the acid- and alkali-resistant cable sheath material.
[0088] Example 2
[0089] An acid and alkali resistant cable sheath material, composed of the following raw materials, by mass: 102 parts of chlorosulfonated polyethylene, 38 parts of ethylene-vinyl acetate copolymer, 62 parts of composite filler, 15 parts of plasticizer, 12 parts of acid absorber, 11.5 parts of flame retardant, 6.5 parts of stabilizer, 3.5 parts of cross-linking agent, 3.9 parts of auxiliary cross-linking agent, 2.5 parts of antioxidant, 1.4 parts of coupling agent, 1.1 parts of antioxidant;
[0090] The chlorine content of the chlorosulfonated polyethylene is 35.4%, the sulfur content is 1.1%, and the Mooney viscosity is ML 1+4 100℃ is 55;
[0091] The vinyl acetate content of the ethylene-vinyl acetate copolymer is 50%, and the Mooney viscosity is ML 1+4 100℃ is 27;
[0092] The preparation method of the composite filler is:
[0093] 1. Preparation of intercalated hydrotalcite:
[0094] (1) Preparation of hydrotalcite dispersion: 10.5 g of hydrotalcite and 220 mL of deionized water were added to an ultrasonic oscillator, the ultrasonic oscillation frequency of the ultrasonic oscillator was controlled to 20 kHz, and ultrasonic oscillation was performed at room temperature for 35 min to obtain a hydrotalcite dispersion;
[0095] The average particle size of the hydrotalcite is 300 nm;
[0096] (2) Intercalation: 48 g of hexadecyltrimethylammonium bromide and 1950 mL of deionized water were added to a reactor, the stirring speed of the reactor was controlled to 350 rpm, and the mixture was stirred at room temperature for 12 min. 620 mL of ammonia water and 920 mL of anhydrous ethanol were added, and the stirring was continued for 25 min. 17 g of melamine and 1350 mL of hydrotalcite dispersion were added, and the stirring was continued for 40 min. The temperature of the reactor was controlled to 52 °C, and the stirring was continued for 5 h. The mixture was transferred to a centrifuge, and the centrifugal speed of the centrifuge was controlled to 7500 rpm. The mixture was centrifuged for 10 min. The precipitate was washed three times with deionized water and vacuum dried to obtain intercalated hydrotalcite.
[0097] The mass concentration of the ammonia water is 25%;
[0098] 2. Preparation of carbon black dispersion: Add 32 g of carbon black and 525 mL of deionized water into an ultrasonic oscillator, control the ultrasonic oscillation frequency of the ultrasonic oscillator to 20 kHz, and ultrasonically oscillate at room temperature for 35 min to obtain a carbon black dispersion;
[0099] The average particle size of the carbon black is 100 nm;
[0100] 3. Primary mixing: add 28 g of intercalated hydrotalcite and 950 mL of deionized water into a reactor, control the stirring speed of the reactor to 350 rpm, stir at room temperature for 35 min, add 8.5 g of hexadecyltrimethylammonium bromide, continue stirring for 35 min, slowly add 900 mL of carbon black dispersion, control the addition speed to 22 mL / min, continue stirring for 1 h after the addition is completed, transfer to a centrifuge, control the centrifugal speed of the centrifuge to 9500 rpm, centrifuge for 10 min, wash the precipitate 3 times with deionized water and vacuum dry to obtain a primary mixture;
[0101] 4. Secondary mixing: 88 g of the primary mixture and 2800 mL of deionized water were added to a reactor, the stirring speed of the reactor was controlled to 350 rpm, and the mixture was stirred at room temperature for 35 min. 3400 mL of sodium dodecylbenzene sulfonate aqueous solution was slowly added at a speed of 95 mL / min. After the addition was completed, the mixture was stirred for 1.5 h. The mixture was transferred to a centrifuge, the centrifugal speed of the centrifuge was controlled to 9500 rpm, and the mixture was centrifuged for 10 min. The precipitate was washed 3 times with deionized water and vacuum dried to obtain a composite filler.
[0102] The mass concentration of the sodium dodecylbenzenesulfonate aqueous solution is 1%;
[0103] The plasticizer is composed of oxidized polyethylene wax, trioctyl trimellitate, and dioctyl sebacate, wherein the mass ratio of oxidized polyethylene wax, trioctyl trimellitate, and dioctyl sebacate is 3.2:22:5.5;
[0104] The acid absorbent is active magnesium oxide with an average particle size of 200 nm;
[0105] The preparation method of the flame retardant is:
[0106] 1. Mixing: Add 82 g of magnesium hydroxide and 11 g of zinc borate into a mixing kettle, control the stirring speed of the mixing kettle to 80 rpm, and stir for 35 min to obtain a mixture;
[0107] The average particle size of the magnesium hydroxide is 100 nm;
[0108] The average particle size of the zinc borate is 100 nm;
[0109] 2. Surface treatment: 92g of the mixture, 19g of Tween 80, and 2800mL of deionized water were added to a reactor, the stirring speed of the reactor was controlled to 300rpm, and the mixture was stirred at room temperature for 1h. The mixture was transferred to a centrifuge, the centrifugal speed of the centrifuge was controlled to 9500rpm, and the mixture was centrifuged for 10min. The precipitate was washed 3 times with deionized water and vacuum dried to obtain a primary filter residue. Then, all the primary filter residues, 18g of phytic acid, and 2800mL of deionized water were added to a reactor, the stirring speed of the reactor was controlled to 300rpm, and the mixture was stirred at room temperature for 2h. , transferred to a centrifuge, the centrifugal speed of the centrifuge was controlled to 9500rpm, centrifuged for 10min, the precipitate was washed 3 times with deionized water and vacuum dried to obtain a secondary filter residue; then all the above secondary filter residues, 24g Tween 80, and 2800mL ethyl acetate were added to a reactor, the stirring speed of the reactor was controlled to 300rpm, stirred at room temperature for 1.5h, transferred to a centrifuge, the centrifugal speed of the centrifuge was controlled to 11000rpm, centrifuged for 10min, the precipitate was washed 3 times with ethyl acetate and vacuum dried to obtain a flame retardant;
[0110] The stabilizer is composed of zinc methacrylate, calcium stearate, zinc stearate, and barium stearate, wherein the mass ratio of zinc methacrylate, calcium stearate, zinc stearate, and barium stearate is 2.9:1.1:0.3:1.2;
[0111] The cross-linking agent is di-tert-butyl diisopropylbenzene peroxide;
[0112] The auxiliary cross-linking agent is trimethylolpropane trimethacrylate;
[0113] The antioxidant is antioxidant 1035;
[0114] The coupling agent is composed of silane coupling agent KH550 and silane coupling agent Si-69, wherein the mass ratio of silane coupling agent KH550 to silane coupling agent Si-69 is 2.2:1;
[0115] The antioxidant is antioxidant OD.
[0116] A preparation method of the aforementioned acid- and alkali-resistant cable sheath material, specifically: after weighing all raw materials according to the specified mass fractions, add chlorosulfonated polyethylene, ethylene-vinyl acetate copolymer, composite filler, plasticizer, acid absorber, flame retardant, stabilizer, antioxidant, coupling agent, and antioxidant into an internal mixer, control the internal mixer temperature to 92°C, and the internal mixer speed to 70rpm. After internal mixer mixing for 28 minutes, cool the mixture to 79°C at a cooling rate of 3.5°C / min, add a crosslinking agent and an auxiliary crosslinking agent, continue internal mixer mixing for 8 minutes, transfer the mixture into an open mixer, perform thin pass, rubber swing, and calendering, and obtain the acid- and alkali-resistant cable sheath material.
[0117] Example 3
[0118] An acid and alkali resistant cable sheath material, composed of the following raw materials, by weight: 105 parts of chlorosulfonated polyethylene, 40 parts of ethylene-vinyl acetate copolymer, 65 parts of composite filler, 16 parts of plasticizer, 13 parts of acid absorber, 12 parts of flame retardant, 7 parts of stabilizer, 3.6 parts of cross-linking agent, 4 parts of auxiliary cross-linking agent, 2.6 parts of antioxidant, 1.5 parts of coupling agent, 1.2 parts of antioxidant;
[0119] The chlorine content of the chlorosulfonated polyethylene is 35.4%, the sulfur content is 1.1%, and the Mooney viscosity is ML 1+4 100℃ is 55;
[0120] The vinyl acetate content of the ethylene-vinyl acetate copolymer is 50%, and the Mooney viscosity is ML 1+4 100℃ is 27;
[0121] The preparation method of the composite filler is:
[0122] 1. Preparation of intercalated hydrotalcite:
[0123] (1) Preparation of hydrotalcite dispersion: Add 11 g of hydrotalcite and 250 mL of deionized water into an ultrasonic oscillator, control the ultrasonic oscillation frequency of the ultrasonic oscillator to 25 kHz, and ultrasonically oscillate at room temperature for 40 min to obtain a hydrotalcite dispersion;
[0124] The average particle size of the hydrotalcite is 400 nm;
[0125] (2) Intercalation: Add 50 g of hexadecyltrimethylammonium bromide and 2000 mL of deionized water into a reactor, control the stirring speed of the reactor to 400 rpm, stir at room temperature for 15 min, add 650 mL of ammonia water and 950 mL of anhydrous ethanol, continue stirring for 30 min, add 18 g of melamine and 1400 mL of hydrotalcite dispersion, continue stirring for 45 min, control the temperature of the reactor to 55 ° C, continue stirring for 5.5 h, transfer to a centrifuge, control the centrifugal speed of the centrifuge to 8000 rpm, centrifuge for 11 min, wash the precipitate with deionized water 4 times and vacuum dry it to obtain intercalated hydrotalcite;
[0126] The mass concentration of the ammonia water is 25%;
[0127] 2. Preparation of carbon black dispersion: Add 35 g of carbon black and 550 mL of deionized water into an ultrasonic oscillator, control the ultrasonic oscillation frequency of the ultrasonic oscillator to 25 kHz, and ultrasonically oscillate at room temperature for 40 min to obtain a carbon black dispersion;
[0128] The average particle size of the carbon black is 200 nm;
[0129] 3. Primary mixing: add 30 g of intercalated hydrotalcite and 1000 mL of deionized water into a reactor, control the stirring speed of the reactor to 400 rpm, stir at room temperature for 40 min, add 9 g of hexadecyltrimethylammonium bromide, continue stirring for 40 min, slowly add 950 mL of carbon black dispersion, control the addition speed to 25 mL / min, continue stirring for 1.5 h after the addition is completed, transfer to a centrifuge, control the centrifugal speed of the centrifuge to 10000 rpm, centrifuge for 11 min, wash the precipitate 4 times with deionized water and vacuum dry to obtain a primary mixture;
[0130] 4. Secondary mixing: 90 g of the primary mixture and 3000 mL of deionized water were added to a reactor, the stirring speed of the reactor was controlled to 400 rpm, and the mixture was stirred at room temperature for 40 min. 3500 mL of sodium dodecylbenzene sulfonate aqueous solution was slowly added at a rate of 100 mL / min. After the addition was completed, the mixture was stirred for 2 h. The mixture was transferred to a centrifuge, the centrifugal speed of the centrifuge was controlled to 10000 rpm, and the mixture was centrifuged for 11 min. The precipitate was washed 4 times with deionized water and vacuum dried to obtain a composite filler.
[0131] The mass concentration of the sodium dodecylbenzenesulfonate aqueous solution is 1%;
[0132] The plasticizer is composed of oxidized polyethylene wax, trioctyl trimellitate, and dioctyl sebacate, wherein the mass ratio of oxidized polyethylene wax, trioctyl trimellitate, and dioctyl sebacate is 3.5:25:6;
[0133] The acid absorber is active magnesium oxide with an average particle size of 200 nm;
[0134] The preparation method of the flame retardant is:
[0135] 1. Mixing: Add 85 g of magnesium hydroxide and 12 g of zinc borate into a mixing kettle, control the stirring speed of the mixing kettle to 100 rpm, and stir for 40 min to obtain a mixture;
[0136] The average particle size of the magnesium hydroxide is 200 nm;
[0137] The average particle size of the zinc borate is 200 nm;
[0138] 2. Surface treatment: 95 g of the mixture, 20 g of Tween 80, and 3000 mL of deionized water were added to a reactor, the stirring speed of the reactor was controlled to 400 rpm, and the mixture was stirred at room temperature for 1.5 h. The mixture was transferred to a centrifuge, the centrifugal speed of the centrifuge was controlled to 10000 rpm, and the mixture was centrifuged for 11 min. The precipitate was washed 4 times with deionized water and vacuum dried to obtain a primary filter residue. Then, all the primary filter residues, 19 g of phytic acid, and 3000 mL of deionized water were added to a reactor, the stirring speed of the reactor was controlled to 400 rpm, and the mixture was stirred at room temperature for 2 .5h, transferred to a centrifuge, the centrifugal speed of the centrifuge was controlled to 10000rpm, centrifuged for 11min, the precipitate was washed 4 times with deionized water and vacuum dried to obtain a secondary filter residue; then all the above secondary filter residues, 25g Tween 80, and 3000mL ethyl acetate were added to a reactor, the stirring speed of the reactor was controlled to 400rpm, stirred at room temperature for 2h, transferred to a centrifuge, the centrifugal speed of the centrifuge was controlled to 11000rpm, centrifuged for 11min, the precipitate was washed 4 times with ethyl acetate and vacuum dried to obtain a flame retardant;
[0139] The stabilizer is composed of zinc methacrylate, calcium stearate, zinc stearate, and barium stearate, wherein the mass ratio of zinc methacrylate, calcium stearate, zinc stearate, and barium stearate is 3:1.2:0.4:1.3;
[0140] The cross-linking agent is di-tert-butyl diisopropylbenzene peroxide;
[0141] The auxiliary cross-linking agent is trimethylolpropane trimethacrylate;
[0142] The antioxidant is antioxidant 1010;
[0143] The coupling agent is composed of silane coupling agent KH550 and silane coupling agent Si-69, wherein the mass ratio of silane coupling agent KH550 to silane coupling agent Si-69 is 2.5:1;
[0144] The antioxidant is antioxidant TPPD.
[0145] A preparation method of the aforementioned acid- and alkali-resistant cable sheath material, specifically comprising: after weighing all raw materials according to the specified mass fractions, adding chlorosulfonated polyethylene, ethylene-vinyl acetate copolymer, composite filler, plasticizer, acid absorber, flame retardant, stabilizer, antioxidant, coupling agent, and antioxidant into an internal mixer, controlling the internal mixer temperature to 95°C, and the internal mixer speed to 80rpm, after internal mixer mixing for 30 minutes, cooling to 80°C at a cooling rate of 4°C / min, adding a cross-linking agent and an auxiliary cross-linking agent, and continuing internal mixer mixing for 8 minutes, transferring to an open mixer, and performing thinning, swinging rubber, and calendering to obtain the acid- and alkali-resistant cable sheath material.
[0146] Comparative Example 1
[0147] Based on the raw material composition and preparation method of the acid-alkali resistant cable sheath material of Example 2, adjustments are made. The specific adjustments are: using a mixture of hydrotalcite and carbon black of equal mass to replace the composite filler;
[0148] In the mixture of hydrotalcite and carbon black, the mass ratio of hydrotalcite to carbon black is 28:55;
[0149] The average particle size of the hydrotalcite is 300 nm;
[0150] The average particle size of the carbon black is 100 nm.
[0151] Other technical solutions are the same as those in Example 2.
[0152] Comparative Example 2
[0153] Based on the raw material composition and preparation method of the acid- and alkali-resistant cable sheath material of Example 2, adjustments are made. The specific adjustments are: using a mixture of magnesium hydroxide and zinc borate of equal quality instead of the flame retardant;
[0154] The mass ratio of magnesium hydroxide to zinc borate in the mixture of magnesium hydroxide and zinc borate is 82:11;
[0155] The average particle size of the magnesium hydroxide is 100 nm;
[0156] The average particle size of the zinc borate is 100 nm.
[0157] Other technical solutions are the same as those in Example 2.
[0158] Performance Test 1
[0159] The Shore A hardness, tensile strength, elongation at break, oxygen index, and tear strength of the acid-alkali resistant cable sheath materials prepared in Examples 1-3 and Comparative Examples 1-2 were sampled and tested, and the test results are as follows:
[0160]
[0161] Performance Test 2
[0162] The tensile strength and elongation at break of the acid-alkali resistant cable sheath materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested respectively as the initial tensile strength and elongation at break, and then completely immersed in a sulfuric acid aqueous solution with a mass concentration of 30%. After being completely immersed at room temperature for 24 hours, the tensile strength and elongation at break of the acid-alkali resistant cable sheath materials were tested again as the tensile strength and elongation at break after acid treatment, and the retention rate of the tensile strength and elongation at break after acid treatment was calculated, and the calculation results are as follows:
[0163]
[0164] Performance Test 3
[0165] The tensile strength and elongation at break of the acid and alkali resistant cable sheath materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested respectively as the initial tensile strength and elongation at break, and then completely immersed in a sodium hydroxide aqueous solution with a mass concentration of 40%. After being completely immersed at room temperature for 24 hours, the tensile strength and elongation at break of the acid and alkali resistant cable sheath materials were tested again as the tensile strength and elongation at break after alkali treatment, and the retention rate of the tensile strength and elongation at break after alkali treatment was calculated, and the calculation results are as follows:
[0166]
[0167] Performance Test 4
[0168] The tensile strength and elongation at break of the acid and alkali resistant cable sheath materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested respectively as the initial tensile strength and elongation at break, and then aged for 168 h using hot air at 136°C, and then the tensile strength and elongation at break of the acid and alkali resistant cable sheath materials were tested as the tensile strength and elongation at break after heat aging treatment, and the retention rates of the tensile strength and elongation at break after heat aging treatment were calculated, and the calculation results are as follows:
[0169]
[0170] Performance Test 5
[0171] The tensile strength and elongation at break of the acid-alkali resistant cable sheath materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested respectively as the initial tensile strength and elongation at break, and then frozen at -50°C for 48h, and then the tensile strength and elongation at break of the acid-alkali resistant cable sheath materials were tested as the tensile strength and elongation at break after freezing treatment, and the retention rates of the tensile strength and elongation at break after freezing treatment were calculated, and the calculation results are as follows:
[0172]
[0173] Performance Test 6
[0174] The tensile strength and elongation at break of the acid and alkali resistant cable sheath materials prepared in Examples 1-3 and Comparative Examples 1-2 were sampled and tested as the initial tensile strength and elongation at break, and then completely immersed in air compressor oil at 70°C for 24 hours. The tensile strength and elongation at break of the acid and alkali resistant cable sheath materials were tested as the tensile strength and elongation at break after the oil resistance test, and the retention rates of the tensile strength and elongation at break after the oil resistance test were calculated. The calculation results are as follows:
[0175]
[0176] Performance Test 7
[0177] The acid- and alkali-resistant cable sheath materials prepared in Examples 1-3 and Comparative Examples 1-2 were sampled and cut, and the dispersion state of carbon black was observed and rated. The rating was divided into 10 levels, and the rating standards were as follows:
[0178] Level 1-2: Very poor;
[0179] Level 3-4: Poor;
[0180] Level 5-6: Uncertain;
[0181] Level 7: Acceptable;
[0182] Level 8: Good;
[0183] Level 9-10: Very good;
[0184] The rating results are as follows:
[0185]
[0186] It can be seen from the above results that, compared with Examples 1-3, in Comparative Example 1, no composite filler was added, and the Shore A hardness, tensile strength, elongation at break, oxygen index, and tear strength were all lower, and the acid and alkali resistance, heat aging resistance, cold resistance, oil resistance, and carbon black dispersion were all poor;
[0187] Compared with Examples 1-3, no flame retardant was added to Comparative Example 2, and the Shore A hardness, tensile strength, elongation at break, oxygen index, and tear strength were all lower, and the acid and alkali resistance, heat aging resistance, cold resistance, oil resistance, and carbon black dispersion were all poor.
[0188] Unless otherwise specified, all percentages used in the present invention are by mass.
[0189] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An acid and alkali resistant cable sheath material, characterized in that: The invention is composed of the following raw materials by weight: 100-105 parts of chlorosulfonated polyethylene, 36-40 parts of ethylene-vinyl acetate copolymer, 60-65 parts of composite filler, 14-16 parts of plasticizer, 11-13 parts of acid absorber, 11-12 parts of flame retardant, 6-7 parts of stabilizer, 3.4-3.6 parts of cross-linking agent, 3.8-4 parts of auxiliary cross-linking agent, 2.4-2.6 parts of antioxidant, 1.3-1.5 parts of coupling agent and 1-1.2 parts of antioxidant; The preparation method of the composite filler comprises the following steps: preparing intercalated hydrotalcite powder, preparing carbon black dispersion, mixing once, and mixing twice; The method for preparing intercalated hydrotalcite powder comprises the following steps: preparing a hydrotalcite powder dispersion, and intercalating the hydrotalcite powder; The method for preparing the hydrotalcite dispersion comprises mixing the hydrotalcite and deionized water evenly to obtain the hydrotalcite dispersion; The intercalation comprises mixing hexadecyltrimethylammonium bromide and deionized water, stirring at room temperature, adding ammonia water and anhydrous ethanol, continuing stirring, adding melamine and hydrotalcite dispersion, continuing stirring, and then continuing stirring at 50-55° C., centrifuging, washing, and vacuum drying the precipitate to obtain intercalated hydrotalcite; The method for preparing the carbon black dispersion comprises mixing carbon black and deionized water uniformly to obtain the carbon black dispersion; The primary mixing comprises mixing the intercalated hydrotalcite powder and deionized water, stirring at room temperature, adding hexadecyltrimethylammonium bromide, continuing stirring, adding the carbon black dispersion, continuing stirring after the addition is completed, centrifuging, washing, and vacuum drying the precipitate to obtain a primary mixture; The secondary mixing comprises mixing the primary mixture and deionized water, stirring at room temperature, adding the sodium dodecylbenzene sulfonate aqueous solution, continuing stirring after the addition is completed, centrifuging, washing, and vacuum drying the precipitate to obtain a composite filler; The method for preparing the flame retardant comprises the following steps: mixing and surface treatment; The mixing is to uniformly mix the magnesium hydroxide and the zinc borate to obtain a mixture; The surface treatment comprises mixing the mixture, the first portion of Tween 80 and the first portion of deionized water, stirring at room temperature, centrifuging, washing and vacuum drying the precipitate to obtain a primary filter residue; then mixing the primary filter residue with phytic acid and the second portion of deionized water, stirring at room temperature, centrifuging, washing and vacuum drying the precipitate to obtain a secondary filter residue; then mixing the secondary filter residue with the second portion of Tween 80 and ethyl acetate, stirring at room temperature, centrifuging, washing and vacuum drying the precipitate to obtain a flame retardant.
2. The acid and alkali resistant cable sheath material according to claim 1, characterized in that: The chlorine content of the chlorosulfonated polyethylene is 35.4%, the sulfur content is 1.1%, and the Mooney viscosity is ML 1+4 100℃ is 55; The vinyl acetate content of the ethylene-vinyl acetate copolymer is 50%, and the Mooney viscosity is ML 1+4 100℃ is 27.
3. The acid and alkali resistant cable sheath material according to claim 1, characterized in that: In the preparation of the hydrotalcite dispersion, the mass volume ratio of hydrotalcite to deionized water is 10-11 g: 200-250 mL; The average particle size of the hydrotalcite powder is 300-400 nm.
4. The acid and alkali resistant cable sheath material according to claim 1, characterized in that: In the intercalation layer, the mass volume ratio of hexadecyltrimethylammonium bromide, deionized water, ammonia water, anhydrous ethanol, melamine, and hydrotalcite dispersion is 47-50g:1900-2000mL:600-650mL:900-950mL:16-18g:1300-1400mL; The mass concentration of the ammonia water is 25%.
5. The acid and alkali resistant cable sheath material according to claim 1, characterized in that: In the preparation of the carbon black dispersion, the mass volume ratio of carbon black to deionized water is 30-35 g:500-550 mL; The average particle size of the carbon black is 100-200 nm.
6. The acid and alkali resistant cable sheath material according to claim 1, characterized in that: In the primary mixing, the mass volume ratio of intercalated hydrotalcite powder, deionized water, hexadecyltrimethylammonium bromide, and carbon black dispersion is 25-30 g:900-1000 mL:8-9 g:850-950 mL; The addition rate of the carbon black dispersion is 20-25 mL / min; In the secondary mixing, the mass volume ratio of the primary mixture, deionized water, and sodium dodecylbenzenesulfonate aqueous solution is 85-90 g: 2700-3000 mL: 3300-3500 mL; The addition rate of the sodium dodecylbenzenesulfonate aqueous solution is 90-100 mL / min; The mass concentration of the sodium dodecylbenzenesulfonate aqueous solution is 1%.
7. The acid and alkali resistant cable sheath material according to claim 1, characterized in that: The plasticizer is composed of oxidized polyethylene wax, trioctyl trimellitate, and dioctyl sebacate, wherein the mass ratio of oxidized polyethylene wax, trioctyl trimellitate, and dioctyl sebacate is 3-3.5:20-25:5-6; The acid absorbent is active magnesium oxide, and the average particle size is 200 nm.
8. The acid and alkali resistant cable sheath material according to claim 1, characterized in that: In the mixing, the mass ratio of magnesium hydroxide to zinc borate is 80-85:10-12; The average particle size of the magnesium hydroxide is 100-200nm; The average particle size of the zinc borate is 100-200 nm; In the surface treatment, the mass volume ratio of the mixture, the first portion of Tween 80, the first portion of deionized water, phytic acid, the second portion of deionized water, the second portion of Tween 80, and ethyl acetate is 90-95g:18-20g:2700-3000mL:17-19g:2700-3000mL:22-25g:2700-3000mL.
9. The acid and alkali resistant cable sheath material according to claim 1, characterized in that: The stabilizer is composed of zinc methacrylate, calcium stearate, zinc stearate and barium stearate, wherein the mass ratio of zinc methacrylate, calcium stearate, zinc stearate and barium stearate is 2.8-3:1-1.2:0.3-0.4:1-1.3; The cross-linking agent is di-tert-butyl diisopropylbenzene peroxide; The auxiliary cross-linking agent is trimethylolpropane trimethacrylate; The antioxidant is one of antioxidant 1035 or antioxidant 1010; The coupling agent is composed of silane coupling agent KH550 and silane coupling agent Si-69, wherein the mass ratio of silane coupling agent KH550 to silane coupling agent Si-69 is 2-2.5:1; The antioxidant is one of antioxidant MB, antioxidant OD and antioxidant TPPD.
10. A method for preparing the acid- and alkali-resistant cable sheath material according to any one of claims 1 to 9, specifically comprising: after weighing all raw materials according to the specified mass fractions, adding chlorosulfonated polyethylene, ethylene-vinyl acetate copolymer, composite filler, plasticizer, acid absorber, flame retardant, stabilizer, antioxidant, coupling agent, and antioxidant into an internal mixer, controlling the internal mixer temperature to 90-95°C, and the internal mixer speed to 60-80rpm, after internal mixer mixing for 25-30min, cooling the mixture to 78-80°C at a cooling rate of 3-4°C / min, adding a crosslinking agent and an auxiliary crosslinking agent, and continuing internal mixer mixing for 7-8min, transferring the mixture into an open mixer, and performing thin pass, rubber swing, and calendering to obtain the acid- and alkali-resistant cable sheath material.
